Wages, race, skills and space : lessons from employers in Detroit's auto industry - Meiklejohn, Susan Turner (Garland reference library of social science ;, 2000)
This book describes findings of a survey-based qualitative research study conducted among Detroit employers in the auto industry to evaluate explanations for why blacks are no longer catching up with whites in terms of income and employment.